PARENTAL ALCOHOLISM AS A RISK FACTOR FOR SOCIAL PERFORMANCE IN ADOLESCENTS - Páez-Landeta, Rubén; Páez Llerena, Alejandro; Riofrio Mora, Ivan; Llerena Montes, Gardenia (Horizonte Sanitario, 2021)
ABSTRACT: Objective: Analyze the relationship between parental alcoholism and social performance in adolescents (who assist to school) from 12 to 17 years of age, in Quito year 2018. Subjects, materials and methods: Desing, analytical, retrospective of cases and controls was used. Participants include 274 students from the secondary level of education, 137 selected as cases and 137 as controls. The ESPERI test was applied for diagnosis or early detection of behavioral disorders in adolescents, and the AUDIT test to evaluate alcoholism in parents. An informed consent was applied to parents and authorities of educational institutions. Results: Significant association was detected between parental alcoholism and social performance, using Chi2 test (95%) = 16.92 p <0.05. Parental alcoholism is a risk factor for social performance. OR = 2.99. CI (95%) = 2.21- 3.77. Conclusions. The relationship between parental alcoholism and the problems derived from it is significant, but are not unicausal, uniform, simple and linear. It is necessary to study more about the disorders that alcoholism generates in mental health of girls, boys and adolescents (depression, anxiety, impulsiveness, challenging attitudes, aggressive behaviors, attention deficit).